2018
DOI: 10.1101/342469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping of TNTs using Correlative Cryo-Electron Microscopy Reveals a Novel Structure

Abstract: The harmonious orchestration of intercellular communication is essential for multicellular organisms. One mechanism by which cells communicate is through long, actin-rich membranous protrusions, called tunneling nanotubes, that allow for the intercellular transport of various cargoes, including viruses, organelles, and proteins between the cytoplasm of distant cells in vitro and in vivo. Over the last decade, studies have focused on their functional role but information regarding their structure and the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 51 publications
3
14
0
Order By: Relevance
“…The recent use of correlative light and cryo-electron microscopy has provided several structural details about TNT morphology, that suggest that the terms «thin» and «thick» TNTs should be used with caution [31]. In this study, TNTs were preserved closer to their native status owing to fixation by rapid freezing.…”
Section: Unique Morphology Of Tntsmentioning
confidence: 72%
See 4 more Smart Citations
“…The recent use of correlative light and cryo-electron microscopy has provided several structural details about TNT morphology, that suggest that the terms «thin» and «thick» TNTs should be used with caution [31]. In this study, TNTs were preserved closer to their native status owing to fixation by rapid freezing.…”
Section: Unique Morphology Of Tntsmentioning
confidence: 72%
“…Moreover, cryo-electron tomography in neuronal cells showed that both thin and thicker iTNTs contained only actin and not microtubules [31], differently from what was proposed as a distinctive feature of thick TNTs in macrophages [35]. Of specific interest, mitochondria were shown to be transported within iTNTs presumably on actin rails, in a tubulin-independent mechanism.…”
Section: Unique Morphology Of Tntsmentioning
confidence: 79%
See 3 more Smart Citations